Prevalence of Health Risk Behaviours among Adolescents of Shivamogga: A Cross-Sectional Study - Kanchana Nagendra; Raghavendraswamy Koppad (Medsci Publications, 2018)
Introduction: Adolescents constitute 20.9% of the Indian population, as per the Census 2011 enumeration data. The problems of adolescents are multi-dimensional in nature and require a holistic approach. Hence, this study was conducted to determine the prevalence and co-occurrence of health risk behaviour among rural and urban adolescents. Methods: The study was conducted in urban and rural field practice areas of Shivamogga institute of medical sciences, Shivamogga. Multistage random sampling done to get sample size of 193 in each urban and rural areas. Data was collected and analyzed in epi info. Results: In urban 2.92% (n=7) of adolescents smoke tobacco whereas in rural 2.50% (n=6) smoke tobacco. Mean age at first smoke in urban was 14.28 (SD±1.57) and in rural was 13.33 (SD±2.05). Prevalence of drinking alcohol in urban was 2.08% (n=5) and in rural was 1.25% (n=3). Mean age at first drink in urban was 12.5 (SD±3.57) and in rural was 10.66 (SD±4.02). Conclusion: There has been an increasing need of inculcating health practices in this age group through different channels to unleash their true potential.